2018
DOI: 10.1080/15384047.2018.1433497
|View full text |Cite
|
Sign up to set email alerts
|

MiR-422a weakened breast cancer stem cells properties by targeting PLP2

Abstract: Up-regulation of miR-422a attenuated microsphere formation, proliferation and tumor formation of breast cancer stem cells via suppressing the PLP2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…Interestingly, miR-449a has been reported to suppress cell migration and invasion in NSCLC by targeting c-Met [8]. Likewise, miR-422a up-regulation has been found to restrain microsphere formation, cell growth and tumorigenesis by inhibiting PLP2 expression in breast cancer [25]. Evidence has been presented supporting SULF2 as a target of miR-422a and can be negatively regulated by miR-422a by dual luciferase reporter gene assay and western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-449a has been reported to suppress cell migration and invasion in NSCLC by targeting c-Met [8]. Likewise, miR-422a up-regulation has been found to restrain microsphere formation, cell growth and tumorigenesis by inhibiting PLP2 expression in breast cancer [25]. Evidence has been presented supporting SULF2 as a target of miR-422a and can be negatively regulated by miR-422a by dual luciferase reporter gene assay and western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have uncovered that miR-422a functions as a tumor suppressor in a variety of F I G U R E 3 Upregulation of miR-422a inhibits RB proliferation in vitro. 19 Here in this study we found that miR-422a negatively modulated SKP2 and suppressed proliferation of RB cells. B, Clonogenic capacity of cells treated with miR-422a mimics or NC-mimics was measured by colony formation assay.…”
Section: Discussionsupporting
confidence: 48%
“…Clinical data analysis found that miR-765 had a negative association with PLP2 in human ccRCC samples. PLP2 was shown to function as an oncogene in hepatocellular carcinoma [30], breast cancer [31] and glioma [32]. However, the function of PLP2 and miRNAs in regulating PLP2 expression in ccRCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%